Analisi Status Pelanggan Menggunakan Metode Decision Tree Dengan Algoritma C45 Studi Kasus Pada PT.Wisanamitra Argakarya - Akhmad Budi (Jurnal Informatika dan Bisnis, 2014)
Along with the development of information technology related to business development thatprovides a lot of choice of alternative solutions to the organization's use of information technology andthe company has become one of the main requirements as a means to increase the value added in thebusiness process. Use of Data Mining can be interpreted as a method of how to improve the quality ofbusiness decisions based on data-related systems. Data Mining processes data into information, and thenthey are processed more further into knowledge that will help the process of analysis of the companyeffectively. This research used C4.5 algorithm to form a decision tree. The decision tree is aclassification and prediction methods. Decision tree method changes the very large fact into a decisiontree that represents the rules. The purpose of this research is analyzing the customers of PT. WisanamitraArgakarya.